EXPRESSIVE SPEECH ACTS IN DANIELLE STEEL'S A PERFECT LIFE - Al Mirrah, Mailisa; Pawiro, Muhammad Ali; Ezir, Ely (Universitas Islam Sumatera Utara, 2024)
This study explores the use of expressive speech acts in Danielle Steel’s novel A Perfect Life, aiming to uncover how these acts contribute to character development and narrative progression. The primary objective is to analyze the prevalence and functions of expressive speech acts—such as expressions of pleasure, pain, joy, sorrow, like, dislike, and apology—within the text. The theoretical framework is grounded in speech act theory, particularly focusing on expressive speech acts as defined by J. L. Austin and further developed by John Searle. This research employs a qualitative approach to dissect and categorize the expressive language used by the novel’s main characters. The analysis reveals a notable dominance of dislike and apology among the expressive speech acts, with a lesser focus on pain, joy, and pleasure. Dislike emerges as the most frequently utilized act, reflecting significant emotional and narrative weight in the characters' interactions. The study's findings suggest that expressive speech acts are crucial in conveying emotional depth and relational dynamics within the novel. The implications of this research highlight the role of expressive speech acts in enhancing narrative engagement and character development. Understanding these dynamics offers valuable insights for literary analysis and can inform future studies on character expression in fiction. The study anticipates that further research could explore the comparative application of expressive speech acts across different genres and authors, expanding the understanding of emotional expression in literature.